PENGARUH TOKO GARUDA JAYA TERHADAP SOSIAL EKONOMI DALAM MENDUKUNG PERKEMBANGAN EKONOMI LOKAL DAN PEMBERDAYAAN PEREMPUAN - Wawan Setiawan; Marsela Putri Gambo; Ni Kadek Widya Swarupini; Caroline Novita Dewi (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2025)
The purpose of this study is to determine how Garuda Jaya Store can influence socio-economics in an effort to support local economic development and to determine how to build women's entrepreneurial spirit in encouraging creativity within themselves. This study uses quantitative data and primary data sources which will then be formulated regarding the influence of Garuda Jaya Store in supporting local economic development and women's empowerment. The results of this study indicate that Garuda Jaya Store is very influential in the field of local economic growth and women's empowerment where Garuda Jaya Store often provides training to the surrounding community, especially women. The existence of Garuda Jaya Store can be beneficial for Housewives to help the family economy.